PARTICIPATION OF TEAM BUILDING AMONG EMPLOYEES IN INFORMATION TECHNOLOGY INDUSTRY IN CHINA - Jane Teng Yan Fang; Lu Yu Ying (International Journal of Accounting, Finance and Business, 2020)
The present study examined the factors affecting the participation of team building among employees in information technology university industry in China. This study focuses on investigating the participation of team building. Three main constructs that are personal characteristics, team characteristics and types of rewards are the independent variables. Moreover, type of activities has been adopted as moderating factor to show how it affects the relationship of independent variables and participation of team building. The quantitative approach is adopted for the present research. A number of 384 employees among information technology industry will be chosen as sample. The Statistical Package for the Social Sciences (SPSS) version 20.0 will be used to analyze the data. In addition, the relationship between dependent variable and independent variables will be examined by Pearson Correlation; the moderation effect on the relationship will be examined by Multiple Regression. Finally, a model on the factors influencing the participation of team building in specific context will be proposed. Hence, the conceptual paper aims to highlights the framework for this investigation. Consequently, the results yielded provide valuable information for participation of team building among employees in information technology industry in China.